Evaluating Writing Proficiency: The Influence of Flipped Classroom Approach on Efl Students’ Complexity and Accuracy - Shafiqah, Syifani; Nasution, Dewi Kesuma (Journal of English Language and Education, 2025)
This study aims to evaluate the influence of the Flipped Classroom approach on the writing proficiency of EFL students, particularly focusing on the aspects of complexity and accuracy. The research employed a One-Group Pretest-Posttest Design and was conducted at Darul Muhmin School, Satun, Thailand. A total of 20 students participated in the study. They were given a pretest to measure their initial writing proficiency, followed by a series of lessons using the Flipped Classroom approach, and finally a posttest to assess improvements. The instructional method involved students learning theoretical content independently through videos and digital modules outside the classroom, while class time was used for writing practice, discussion, and feedback. The data were analyzed using SPSS version 29.00, with a Paired Sample T-test employed to determine the significance of the treatment. The results showed a significant improvement in students’ writing scores after the treatment. The mean score increased from 74.50 (pretest) to 90.25 (posttest), and the significance value (2-tailed) was 0.001, which is less than 0.05. These findings indicate that the Flipped Classroom approach had a meaningful effect on enhancing the complexity and accuracy of students’ writing. Therefore, the Flipped Classroom can be considered an effective pedagogical strategy in EFL writing instruction.